Epigenetics in human disease - Tollefsbol, Trygve O. (Translational epigenetics, 2023)
Epigenetics in Human Disease, Third Edition examines the diseases and conditions on which we have advanced knowledge of epigenetic mechanisms, such as cancer, autoimmune disorders, aging, metabolic disorders, neurobiological disorders and cardiovascular disease. From molecular mechanisms and epigenetic technology to clinical translation of recent research, the nature and applications of the science is presented for those with interests ranging from the fundamental basis of epigenetics to therapeutic interventions for epigenetic-based disorders, with an emphasis throughout on understanding and application of key concepts in new research and clinical practice. Fully revised and up-to-date, this Third Edition discusses topics of current interest in epigenetic disease research, including stem cell epigenetic therapy, bioinformatic analysis of NGS data, epigenetic mechanisms of imprinting disorders, microRNA in cancer, epigenetic approaches to control obesity, epigenetics and airway disease, and epigenetics in cardiovascular disease. Further sections explore online epigenetic tools and datasets; early-life programming of epigenetics in age-related diseases; the epigenetics of addiction and suicide, and epigenetic approaches to regulating and preventing diabetes, cardiac disease, allergic disorders, Alzheimer's disease, respiratory diseases, and many other human maladies. In addition, each chapter now includes chapter summaries, definitions, and vibrant imagery and figures to reinforce understanding, as well as step-by-step methods and disease research case studies.